Not just about "the science": science education and attitudes to genetically modified foods among women in Australia. Issue 1 (2nd January 2017) - Bray, Heather J.; Ankeny, Rachel A.
Abstract : Previous studies investigating attitudes to genetically modified (GM) foods suggest a correlation between negative attitudes and low levels of science education, both of which are associated with women. In a qualitative focus group study of Australian women with diverse levels of education, we found attitudes to GM foods were part of a complex process of making "good" food decisions, which included other factors such as locally produced, fresh/natural, healthy and nutritious, and convenient. Women involved in GM crop development and those with health science training differed in how they used evidence to categorize GM foods. Our findings contribute to a deeper understanding of how GM food, and the role of science and technology in food production and consumption more broadly, is understood and discussed amongst diverse "publics" and across different "sciences, " and to research related to deepening public engagement at the intersection of science and values.